193k views
4 votes
How to factorised quadratics
in simple form thank you

User EdSF
by
5.2k points

1 Answer

2 votes

Answer:

ax²+ bx + c = 0

Explanation

Multiplying (x+4) and (x−1) together (called Expanding) gets x2 + 3x − 4 :


expand vs factor quadratic


So (x+4) and (x−1) are factors of x2 + 3x − 4


Just to be sure, let us check:


(x+4)(x−1) = x(x−1) + 4(x−1)

= x2 − x + 4x − 4

= x2 + 3x − 4 yes

Yes, (x+4) and (x−1) are definitely factors of x2 + 3x − 4




User Ryan Tenney
by
5.4k points